Dry bulk density and loss-on-ignition measurements from sediment cores of the Onepoto Basin (New Zealand) - Benjamin Laeuchli (PANGAEA, 2022)
The presented LOI and DBD data has been used for the reconstruction of the depositional history of Onepoto maar lake (Northern New Zealand) as a response to regional and global drivers of climatic change, as well as localised events restricted to the lake catchment. The data set has been stacked data from lake sediment cores extracted from Onepoto Basin (Northern New Zealand) in 2018 and archival material extracted from the site in 2011. These core segments form the basis on which the newly established extquotesingleOn18 extquotesingle composite record was developed.